Phase 1b, multicenter, single blinded, placebo‐controlled, sequential dose escalation study to assess the safety and tolerability of topically applied AG013 in subjects with locally advanced head and neck cancer receiving induction chemotherapy - Limaye, Sewanti Atul; Haddad, Robert I.; Cilli, Fiona; Sonis, Stephen T.; Colevas, A. Dimitrios; Brennan, Michael T.; Hu, Kenneth S.; Murphy, Barbara A. (Cancer, 2013)
BACKGROUND Oral mucositis (OM) is a significant toxicity of induction chemotherapy for locally advanced head and neck cancer (LAHNC). The safety and tolerability of AG013, an oral rinse containing recombinant Lactococcus lactis secreting mucosal protectant human trefoil factor 1 (hTFF1), was evaluated in a phase 1b study in LAHNC subjects who received induction with cisplatin, 5‐fluorouracil, with or without docetaxel. Preliminary efficacy data were also obtained. METHODS A total of 25 of 52 LAHNC subjects who were followed during induction cycle 1 developed ulcerative oral mucositis (UOM; World Health Organization grade > 2) and were randomized to AG013:placebo (5:2 ratio) for cycle 2. Dosing schedules of 1, 3, or 6 times daily were evaluated (2 × 1011, 6 × 1011, and 1.2 × 1012 colony forming units per day, respectively). OM was evaluated daily from cycle 2, day 1 through 14, using World Health Organization criteria. Pharmacokinetic assessment was also conducted. RESULTS AG013 bacteria were not detected in blood. Oral live AG013 bacterial and hTFF1 levels in saliva and oral mucosa were equivalent among treatment groups. The most frequently occurring adverse events were nausea, oral pain, fatigue, diarrhea, and mucosal inflammation. Only 12% (3 of 25 adverse events), mainly nausea, were attributed to the investigational medicinal product: AG013 or placebo. Efficacy analysis showed a 35% reduction in percentage of days with UOM in AG013‐subjects versus placebo. All placebo subjects experienced ≥ 2 days of UOM, whereas 29% of AG013 subjects had UOM for 0 or 1 day. AG013 use resulted in fewer unscheduled office and emergency room visits. No differences were noted in mouth and throat soreness, opioid use, or gastrostomy tube placement. CONCLUSIONS AG013 was safe and well tolerated. Preliminary efficacy data support further study. Cancer 2013;119:4268–4276. © 2013 American Cancer Society. An oral rinse formulation of AG013 containing recombinant Lactococcus lactis secreting the mucosal protectant human Trefoil Factor 1 (hTFF1) was evaluated in a phase 1b study in subjects with locally advanced head and neck cancer who were receiving induction chemotherapy with cisplatin, 5‐fluorouracil with or without docetaxel. AG013 rinse was found to be safe and tolerable with preliminary efficacy data warranting further study.